2011
DOI: 10.1103/physrevlett.106.113901
|View full text |Cite
|
Sign up to set email alerts
|

Quantum Light from a Whispering-Gallery-Mode Disk Resonator

Abstract: Optical parametric down-conversion has proven to be a valuable source of nonclassical light. The process is inherently able to produce twin-beam correlations along with individual intensity squeezing of either parametric beam, when pumped far above threshold. Here, we present for the first time the direct observation of intensity squeezing of -1.2  dB of each of the individual parametric beams in parametric down-conversion by use of a high quality whispering-gallery-mode disk resonator. In addition, we observe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
125
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 158 publications
(126 citation statements)
references
References 28 publications
0
125
0
1
Order By: Relevance
“…[ 1 ] Prominent examples are whispering gallery mode (WGM) microcavities, [ 2 , 3 ] which confi ne photons by means of continuous total internal refl ection along a curved and smooth surface. The long photon lifetime (described by high Q factors), strong fi eld confi nement, and in-plane emission characteristics make them promising candidates for novel light sources [4][5][6][7][8][9] and biochemical sensors with the ability of detecting few or even single nanoparticles. [ 10 , 11 ] The principal disadvantage of circular WGM microcavities is their intrinsic isotropy of emission due to their rotational symmetry.…”
Section: Doi: 101002/adma201201229mentioning
confidence: 99%
“…[ 1 ] Prominent examples are whispering gallery mode (WGM) microcavities, [ 2 , 3 ] which confi ne photons by means of continuous total internal refl ection along a curved and smooth surface. The long photon lifetime (described by high Q factors), strong fi eld confi nement, and in-plane emission characteristics make them promising candidates for novel light sources [4][5][6][7][8][9] and biochemical sensors with the ability of detecting few or even single nanoparticles. [ 10 , 11 ] The principal disadvantage of circular WGM microcavities is their intrinsic isotropy of emission due to their rotational symmetry.…”
Section: Doi: 101002/adma201201229mentioning
confidence: 99%
“…Many of the sources based on integrated resonators have so far failed to achieve the narrow linewidths compatible with quantum memories because of their relatively modest Q-factors [14,16,[26][27][28][29]. On the other hand, narrow linewidth sources can be achieved by exploiting extremely high Q-factor cavities, however these are fundamentally incompatible with large-scale integration [6,15,[31][32][33].…”
Section: Introductionmentioning
confidence: 99%
“…On the one hand, photonic chips able to realize the logic ports required for quantum computing have been recently demonstrated [11,12]. On the other hand, an intense research activity has been dedicated to implement on chip sources of single and entangled photons [6,7,[13][14][15][16][17]. A detailed review on the genesis and evolution of integrated quantum optics can be found in [18].…”
Section: Introductionmentioning
confidence: 99%
“…One of the most promising applications of WGM MRs is in the area of optical sensing [2,7,8], where such resonators exhibit a higher sensitivity than their macro-fiber counterparts. WGMs can be supported by a variety of resonator geometries, such as spheres [9], spheroids [10], disks [11], rings [8], and cylinders [12]. The choice of the specific resonator for a given application is typically impacted by three main considerations, such as the maximum achievable Q-factor, simplicity of fabrication, and ease of interconnection [13].…”
Section: Introductionmentioning
confidence: 99%